Homozygous mutation of MYBPC3 associated with severe infantile hypertrophic cardiomyopathy at high frequency among the Amish. Issue 10 (8th May 2008) - Zahka, K; Kalidas, K; Simpson, M A; Cross, H; Keller, B B; Galambos, C; Gurtz, K; Patton, M A; Crosby, A H
Abstract : Background: Familial hypertrophic cardiomyopathy (HCM) is a leading cause of sudden cardiac death among young and apparently healthy people. Autosomal dominant mutations within genes encoding sarcomeric proteins have been identified. An autosomal recessive form of HCM has been discovered in a group of Amish children that is associated with poor prognosis and death within the first year of life. Affected patients experienced progressive cardiac failure despite maximal medical treatment. Postmortem histology showed myofibre disarray and myocyte loss consistent with refractory clinical deterioration in affected infants. Objective: To conduct a genome-wide screen for linkage and try to identify an autozygous region which cosegregates with the infant cardiac phenotype Methods and results: An autozygous region of chromosome 11 which cosegregates with the infant cardiac phenotype was identified. This region contained the MYBPC3 gene, which has previously been associated with autosomal dominant adult-onset HCM. Sequence analysis of the MYBPC3 gene identified a splice site mutation in intron 30 which was homozygous in all affected infants. All surviving patients with the homozygous MYBPC3 gene mutations (3330+2T>G) underwent an orthotopic heart transplantation. Conclusions: Homozygous mutations in the MYBPC3 gene have been identified as the cause of severe infantile HCM among the Amish population.